2016
DOI: 10.4012/dmj.2015-193
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of metal- and fiber-reinforced composite root canal posts on flexural properties

Abstract: The aim of this study was to observe the effects of different test conditions on the flexural properties of root canal post. Metaland fiber-reinforced composite root canal posts of various diameters were measured to determine flexural properties using a threepoint bending test at different conditions. In this study, the span length/post diameter ratio of root canal posts varied from 3.0 to 10.0. Multiple regression models for maximum load as a dependent variable were statistically significant. The models for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Regardless of the fiberglass post types, their elastic modulus, which is comparable to resin and dentin composite systems, makes their combination with polymerized resin cement a mono-block structure in the root. This combination increases the strength of the endodontically treated tooth to that of an IT by reducing stress accumulation and better stress distribution [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. According to our study results, the highest fracture strength was observed in the IT despite the increase in fracture strength of over-flared endodontically treated teeth restored adopting the multipost approach technique.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Regardless of the fiberglass post types, their elastic modulus, which is comparable to resin and dentin composite systems, makes their combination with polymerized resin cement a mono-block structure in the root. This combination increases the strength of the endodontically treated tooth to that of an IT by reducing stress accumulation and better stress distribution [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. According to our study results, the highest fracture strength was observed in the IT despite the increase in fracture strength of over-flared endodontically treated teeth restored adopting the multipost approach technique.…”
Section: Discussionsupporting
confidence: 53%
“…Debilitation of the biomechanical properties of teeth following extensive coronal degradation (more than 50%) requires using a post to enhance the coronal restoration retention and resistance [17,18]. The role of fiber-reinforced resin composites in enhancing the fracture strength of coronal restorations has been confirmed due to the similar biomechanical characteristics of dentin, the ability to evenly distribute the applied stresses [19], and acceptable longterm clinical performance [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Under the over-flaring conditions in root canal therapy, in addition to the unfavorable stress absorption by the weak dentin wall of the root [21], increasing the volume of luting cement consumed to fill the space between the post and canal increases.…”
Section: Discussionmentioning
confidence: 99%
“…The role of fiber-reinforced composite resins in increasing the fracture resistance of coronal restorations has been evaluated [ 4 6 ]. Currently, fiber posts have attracted the attention of clinicians due to their biomechanical properties that are similar to those of dentin, their ability to distribute stresses homogeneously, reducing the risk of irreversible root fractures [ 7 ], and their long-term clinical performance [ 8 , 9 ]. It has been demonstrated that the low elastic modulus of fiber posts results in the concentration of stresses predominantly on the cervical area, leading to debonding of the post [ 10 ] and failure of the restoration at the core area [ 2 ].…”
Section: Introductionmentioning
confidence: 99%